Influence of iron on the alteration of the SON68 nuclear glass in the Callovo-Oxfordian groundwater. (January 2019) - De Echave, T.; Tribet, M.; Gin, S.; Jégou, C.
Abstract: In France, the high level radioactive waste, contained in a glassy matrix, is intended for a deep geological disposal. It is then important to understand glass alteration, which depends on the near-field materials and the environmental conditions. The corrosion of the carbon steel overpack (used in the French multi-barrier concept for the disposal of high level radioactive waste) could influence glass alteration by the release of iron in the solution and the formation of iron corrosion products. For a better understanding of these interactions, different experiments were performed at 90 °C using a SON68 glass (non-radioactive surrogate of the R7T7 glass) separated by 80 μm from a pristine iron foil and immersed in synthetic groundwater. A pre-corroded iron foil and a PTFE foil, replacing the pristine iron foil, were also used. The influence of iron on glass alteration was studied, focusing on two different environments (the confined environment, inside the crack, and the diluted environment, where the faces are exposed to the homogeneous solution) and on the influence of a pre-corrosion of the iron foil. Depending on the previously described conditions, some variations were observed: as a whole, glass alteration increased in the presence of iron due to the precipitation of Fe-silicate minerals and it was also higher in the diluted environment than in the confined environment, indicating that the gel protective properties were different in both cases. This might be related either to differences in the solution composition in contact with the glass or differences in the gel composition, as it was shown that iron can enter the porous gel layer. In the tested conditions, pre-corrosion of an iron foil seemed to have no influence on glass alteration in a confined environment. Highlights: Glass alteration is studied under environmental conditions with iron by considering a dilute and a confined medium. Glass alteration is greater in the presence of an iron source, and in the diluted environment, glass alteration is greater than in the confined environment. The pre-corrosion of the iron foil seems to have no significant influence on glass alteration in the confined environment. Secondary Fe-silicate phases are observed in all experiments containing an iron source.